Pendidikan Kesehatan Dengan Media Buku Saku Terhadap Kepatuhan Diet Hipertensi Di Desa Purwomartani Kalasan - Ratna Lestari; Cantika Audia; Sriyati Sipora (STIKes MERCUBAKTIJAYA, 2023)
Hypertension is a degenerative disease which is life-threatened and seriously caused complications in sufferers. One of the keys to success in controlling hypertension is by managing an appropriate diet, but this is neglected because sufferers feel they are asymptomatic so they comply with hypertension management. Health education with attractive media is needed to increase compliance with hypertension sufferers. This study aims to determine the effect of health education with pocket books on hypertension diet compliance in the Purwomartani region Kalasan. This research is a quantitative research with a pre-experimental type with a one group pre posttest approach without control. The sampling technique used the total population involving 30 people with hypertension. This research instrument uses a hypertension diet compliance questionnaire and a pocket book which has been tested using content validity. The results of the study showed that the mean value of dietary compliance for hypertension sufferers before being given health education using a pocket book was 67.27 with an Sd value of 5.439, and the mean value after being given health education using a pocket book was 80.07 with an Sd value of 5.601. The results of the paired t test showed a mean value of 12.8 with a p value of 0.000 <0.05. It can be concluded that there is an influence of health education with booklets on hypertension diet compliance. It is hoped that health education using pocket book will become one of the standards for providing education.